Kajian Literatur Model Layanan Informasi Lowongan Kerja dengan Fitur Pelacakan Seleksi: Implikasi Pengembangan Kota Solo - Eka Nur Prihatin; Muhammad Daiva Shabri Raya Rabani (Badan Riset dan Inovasi Daerah Kota Surakarta, 2025)
The recruitment process is one of the main functions of Human Resource Management (HRM) that plays an essential role in ensuring the availability of a qualified workforce that aligns with organizational needs. In the City of Surakarta, the dissemination of job vacancy information is still dominated by national-scale private platforms such as Jobstreet, while local platforms like Siap Ditata Surakarta have not yet been optimized in terms of reach and feature quality. One of the persistent issues is the lack of transparency in the employee selection process, which affects the level of accountability and applicants’ trust in the existing recruitment system. An innovation in the form of a selection stage tracking feature can be integrated into the local job vacancy service. This feature not only provides automatic notifications at each stage of the selection process but also allows applicants to see the number of employers who have viewed or shown interest in their CVs. This innovation is expected to strengthen the core principles of HRM—objectivity, transparency, and accountability—in the recruitment process, while supporting fairer and data-driven decision-making. Through a literature review approach, this study recommends the active role of the Department of Manpower and the integration of the tracking system as a strategy to enhance digital-based public HRM practices that are professional and sustainable.